2023
DOI: 10.1038/s41598-023-33605-1
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile adducts: design, synthesis and biological evaluation as antimicrobial, haemolytic and thrombolytic agent

Abstract: In this work, five acrylonitrile adducts were screened for antibacterial activity against Gram-positive Bacillus subtilis, Microbial Type Culture Collection and Gene Bank (MTCC 1305) and Gram-negative Escherichia coli (MTCC 443). Synthesis was followed by aza-Michael addition reaction, where the acrylonitrile accepts an electron pair from the respective amines and results in the formation of n-alkyliminobis-propionitrile and n-alkyliminopropionitrile under microwave irradiation. Characterization of the compoun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
1
0
1
Order By: Relevance
“…22–24 It is reported that nitrile group modified complexes show good antibacterial activity against Gram-positive and Gram-negative bacteria. 25–27 Importantly, the nitrile group can be used as bioactive “warheads” to hydrogen bond with proteins. 28 The nitrile group has significant effects on bacterial communities due to its conjugation effects.…”
Section: Introductionmentioning
confidence: 99%
“…22–24 It is reported that nitrile group modified complexes show good antibacterial activity against Gram-positive and Gram-negative bacteria. 25–27 Importantly, the nitrile group can be used as bioactive “warheads” to hydrogen bond with proteins. 28 The nitrile group has significant effects on bacterial communities due to its conjugation effects.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , <...…”
unclassified